Pemalsuan produk halal di Malaysia: Analisis dari tahun 2007 hingga 2016 / Aisyah Faizah Zaki - Aisyah Faizah , Zaki (2018)
Nowdays, there are a few irresponsible enterprenur especially in manufacturing and distribution product that have abused the certification through forgery of its logo and label. These irresponsible businesses have misled the consumer in believing false pretences halal logo in products offered in order to achieve short term profit gain. This research will focus on the perspective of Islamic law in forgery product. Research also will review previous cases of halal certification and logo counterfeiting from 2007 to 2016. Content resources from various websites, Ministry of Domestic Trade Co-operative and Consumerism (KPDNKK), Malaysian Islamic Consumer Association and local newspaper will be compiled and analysed before forming the end solution for the research matter. Islamic law in relation to halal certification and logo forgery practices will also be explains from the aspect of consumer law as both views shares lots of similarities. Analysis of the research finds the forgery of halal content, certification and its logo to be the most common irresponsible practises of the industry. Malpractice in the industry is mainly caused of two major reasons, firstly non-halal businesses who wish to increase their profit gain by attracting more Islamic consumers and secondly halal businesses that use an illegal copy of halal certification due to difficulty in certifying their businesses or during application being processed. Nowdays Islam regards the illegal practises as a form of oppression against the rights of its believers therefore such malpractices could be considered as haram and illegal. However, in terms of products there are halal and haram. A product is halal if the forged material is sourced from halal sources and processes as well as does not have a safety effect on consumers vice versa. Therefore, a better solution is needed to enforce and strengthened the assurance of halal products. These indications need to be addressed seriously by the authorities and consumers so that the halal ecosystems whether local or global levels are not static.